Noam Chomsky Distorted morality : America's war on terror? - Junkerman, John ([S.l.] : Plug Music Limited, 2002)
The hypocrisy of the U.S. government is powerfully scrutinized in "Distorted Morality", a scathing thesis presented by renowned scholar Noam Chomsky before an intimate audience at Harvard University.
A 55 minute talk at Harvard University -- A Lively 1 hour question and answer session -- Noam chomsky's bibliography, biography, CV.
English.
Subtitle : English, Chinese.
Keywords: Chomsky, Noam, -- 1928-; Documentary films -- Politics; Documentary films -- United States -- Terrorism; Terrorism -- United States; War on Terrorism -- United States